Trophic structure in a pilot system for the integrated multi-trophic aquaculture off the east coast of Korean peninsula as determined by stable isotopes. Issue 1 (15th June 2015) - Park, Hyun Je; Han, Eunah; Lee, Won Chan; Kwak, Jung Hyun; Kim, Hyung Chul; Park, Mi Seon; Kang, Chang-Keun
Highlights: A pilot system for the integrated multi-trophic aquaculture was installed. The black rockfish, sea cucumber, oyster, and macroalgae were co-cultured. Co-cultured sea cucumber at the IMTA site assimilated aquaculture wastes. Fish cage-waste contribution to food web in/around the IMTA system was minor. The sea cucumber was identified as an extractive species of fish cage wastes. Abstract: To assess the potential for nutritional exploitation of caged-fish-derived waste through the use of extractive co-cultured species in a pilot system for an integrated multi-trophic aquaculture (IMTA), we compared their C and N stable isotope ratios with those of uncultured macroinvertebrates in and around the system. Black rockfish were co-cultured with sea cucumber, oyster, and two macroalgae as extractive species. Isotope signatures of the co-cultured sea cucumber at the IMTA site differed from those at the control site, indicating their assimilation of aquaculture wastes. In contrast, δ 13 C and δ 15 N of individual taxa of the cultured oyster and uncultured invertebrates were consistent between sites, suggesting a minor contribution of the aquaculture waste to benthic and pelagic food chains in and around the IMTA system. These results provide evidence of the suitability of using sea cucumber as an extractive species to reduce the impact of a monoculture system on the ambient environment.